Assessing performance of mutual funds in Indonesia - Abd. Majid, M. Shabri; Hartomi, Maulana (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2010)

(untitled)
This study empirically assesses the relative efficiency of mutual funds in Indonesia during the period 2004 to 2007. To measure their efficiencies, the output-input data consisting of a panel of 23 mutual funds are empirically examined based on the most commonly used non-parametric approach, namely, Data Envelopment Analysis (DEA). The study finds that, on average, the mutual funds experienced a decrease in total factor productivity (TFP) growth. It is mainly caused by a declining in both efficiency and technical efficiencies, where the efficiency change is largely contributed by the changes in pure efficiency rather than scale efficiency. The findings of the study suggest that the mutual funds' industry in Indonesia has a great opportunity to promote its TFP by constantly optimizing and upgrading the educational and training programs intended to improve managerial ability and to speed up the adoption of new technologies.